A avaliação da aprendizagem: aplicação de um Modelo Fuzzy para se obter notas mais justas na disciplina de língua portuguesa - Ribeiro, Ana Paula de Medeiros (2007)
This study involves one of the most important themes in the educational field: the learning assessment. From everything that is discussed about it, there is something that is always in evidence: the qualitative proposal that is recommended to the assessment process. So, the aim of this study was to comprehend its meaning from the vision of the elementary school teachers from one municipal school of Fortaleza, in order to be defined the meaning the teachers give to it, as well as the difficulties found during the assessment process. The interpretation of the teachers’ speeches was done by using the hermeneutic theory in the modern version of Martin Heidegger and Hans-Georg Gadamer. Therefore, this study was not limited to identify and describe the assessment meaning, it intended to develop a software based in the fuzzy sets theory, considering the information obtained from the application of the methodological instruments. The software intends to support the teachers during the assessment process, specially in the numerical grades conversion. The fuzzy logic has a coherent application in this situation because it has the power of manipulate qualitative data which are, in this study, the concepts, into quantitative data, the numerical grades. The software preliminary version was tested by the author through a comparative study between the concepts and numerical grades given by the teachers and the ones given by the fuzzy system. The results showed a confidence degree of 93%. It demonstrates that it might be a useful instrument to teachers during the hard work of evaluating their students.